Índice de Vegetação por Diferença Normalizada (NDVI) no patossistema Puccinia triticina Triticum aestivum - Gonçalves, Rodrigo Alff (2015)
One of the major problems and difficulties in the production process is to monitor / predict the presence, intensity and abundance of these pathogens under field conditions in a timely manner to avoid significant damage to production. In this sense, the objective of this research was to characterize the changes in the spectral pattern correlated with the incidence of foliar diseases in wheat. The experimental design was a factorial (5x3) randomized blocks with five doses of nitrogen (0, 25, 50, 75, 100 kg N ha-1) applied at tillering and three management programs with fungicides in the shoot, the untreated control. Scores NDVI readings were performed with the optical sensor GreenSeeker Handheld Crop Sensor in six predetermined locations within each plot of 11 m2 (2,2mx5m). It is possible to detect the presence of Puccinia triticina Erikss from the readings with NDVI GreenSeeker sensor. Scores NDVI can demonstrate that there is a strong correlation between AUDPC and reduced productivity. The GreenSeeker sensor proved efficient in detecting spectral changes from signs and symptoms of Puccinia triticina Erikss.